Legal Protection Against The Crime of Abortion Performed by Child Victims of Rape from Victimological Perspective - Christ Sella; Della Rolansa BR Siboro; Muhammad Iqbal Baiquni (IJCLS (Indonesian Journal of Criminal Law Studies), 2022)
Children are valuable assets that must always be guarded and protected; on the other hand, there is also inherent dignity, dignity, and rights as human beings, which must also uphold. However, he often gets rape treatment. As a result of being unable to accept the suffering experienced, the decision to have an abortion was chosen. In positive law, it does not legalize this abortion, but there are several considerations that judges can use to override the imposition of sanctions on abortions committed by children. Victimological studies can also be used as guidelines to determine the position of girls, whether they are perpetrators or victims of events. Of course, if you are a victim, you should obtain legal protection from the state. In this paper, they will discuss this problem through a case study. The type of writing used is normative juridical, secondary legal, and non-legal materials collected through library research techniques.